77 Factors Impacting Abundance of PAGs After Embryo Transfer in Beef Cattle. (8th March 2022) - Quail, Lacey K; Ketchum, Jaclyn N; Epperson, Kaitlin M; Zoca, Saulo Menegatti; Andrews, Taylor; Kline, Adalaide C; Rich, Jerica J J; Zezeski, Abigail L; Ogg, Makayla; Rhoades, Jim R; Smith, Michael F; Perry, George A; et al.
Abstract: The objective of this study was to determine factors impacting abundance of pregnancy-associated glycoproteins (PAGs) after embryo transfer. Cows were synchronized using the 7-d CO-Synch+CIDR ® protocol and grouped by estrus expression 48h after prostaglandin (d0) [Estrual (PC): n = 198; Non-estrual: n = 406]. Non-estrual cows were administered GnRH and randomly assigned to Estradiol treatment (E2: n=202; 0.1mg estradiol 17-β) or no treatment (NC: n = 204). In vivo produced embryos were transferred on d7, with grade, stage, and flush balanced across treatments. Circulating concentrations of estradiol and progesterone were determined on d0 and d7, respectively. Abundance of PAGs was determined on d24 and d26. Cows that were pregnant on d30 were grouped by age (H: 2, C: >2 years) and subjected to analysis. Correlations were analyzed using PROC CORR in SAS, while PAGs were analyzed using PROC GLIMMIX with treatment, age, year, sire, and embryo grade and stage as fixed effects. Abundance of PAGs on d24 was influenced by treatment (P = 0.01; PC=0.75±0.09, E2=0.59±0.09, NC=0.56±0.08), age (P < 0.01; H=0.75±0.09, C=0.52±0.08), year (P < 0.0001; 2019=0.42±0.08, 2020=0.84±0.09), and sire (P = 0.02; A=0.49±0.12, B=0.62±0.09, C=0.47±0.11, D=0.77±0.08, E=0.83±0.21), but not embryo grade (P = 0.89) or stage (P = 0.40). There was a negative correlation between d0 estradiol and d24 PAGs (P < 0.0001, r=-0.34), and a positive correlation between d7 progesterone and d24 PAGs (P < 0.0001, r=0.36). On d26, PAGs tended to differ by treatment (P = 0.09; PC=2.43±0.20, E2=2.33±0.21, NC=2.03±0.20). Age (P = 0.02; H=2.48±0.22, C=2.05±0.16), and sire (P = 0.0007; B=2.01±0.20, D=2.52±0.17) influenced PAGs, but embryo grade (P = 0.33) and stage (P = 0.32) did not on d26. Sire was associated with PAGs, and presumably embryo attachment, but not pregnancy rate. Increased progesterone concentrations on d7 were correlated with earlier attachment as measured by PAGs. Estrus expression prior to d0 may enhance earlier attachment of the fetal/maternal interface, and supplemental estradiol on d0 may improve attachment by d26 when ovulation is induced. Funded by NIFA 2019-67015-29411.